Antidepressant-induced sexual dysfunction - Kim Outhoff (South African Family Practice)
Depression and sexual dysfunction are both common in the general population. When they co-exist, they have the potential to impact negatively on each other in a bidirectional manner. Medication used to treat depression may cause additional problems with the sexual response cycle; although no drug is completely innocent, serotonergic agents such as selective serotonin reuptake inhibitors (SSRIs) and serotonin and noradrenaline reuptake inhibitors (SNRIs) are most frequently implicated in antidepressant-induced sexual dysfunction. Adherence to long-term treatment may be compromised, which may have serious consequences. Various psychological and pharmacological strategies, including the ad hoc use of sildenafil, may offer some respite.